Rational Emotive Behavior Therapy As A Curative Efforts In Handling Anxiety In Students Who Are Victims Of Broken Homes - La Coy; Heri Fadli Wahyudi (Penerbit Hellow Pustaka, 2025)
This study describes rational emotive behavior therapy as a curative effort in dealing with the anxiety of students of broken home victims in Tarbiyatul Mualimin Islamiyah son of Al-amien Prenduan which is described in two focuses, namely, how the process of rational emotive behavior therapy in dealing with the anxiety of students victims of broken home in Tarbiyatul Mualimin Islamiyah son of Al-Amien Prenduan, and how the final result in the implementation of rational emotive behavior therapy in dealing with the anxiety of students victims of broken homes in Tarbiyatul Mualimin Islamiyah son of Al-Amien Prenduan. One method that can deal with the anxiety of broken home victims is by means of rational emotive behavior therapy counseling services with the ABCDE technique which counseling was developed by Albert Elis. Rational emotive behavior therapy is an approach to change the irrational thinking of counsellors in rational thinking, so as to influence behavior change towards counseling for the better. The approach in this study uses qualitative methods of case study type, while the number of objects in this study consists of four students of Tarbiyatul Mualimin Islamiyah son of Al-Amien Prenduan. As for the findings of this study, the counsellor has done positive affirmations and done things that the counsellor likes or hobbies. Finally, the results of this study there are three counsellors who can be said to have succeeded in doing what the counselor directed, but there is only one counsellor who is less able to understand what the counselor says, and just follows the process without wanting to do what the counselor says.